Evaluación de impacto del género del jefe de hogar sobre la tenencia de vivienda en Ecuador - Castillo Veintimilla, Juan Pablo (2023)
In Ecuador, the problem of housing tenure is related to a possible gender gap, where women have certain barriers and forms of discrimination that hinder their access to housing. Therefore, the general objective of this research is to evaluate the impact of the gender of the head of household on housing tenure in Ecuador, through the use of econometric techniques, in order to recommend policy implications focused on housing tenure in the country. For this purpose, data from the National Survey of Employment, Unemployment and Underemployment (ENEMDU) of the National Institute of Statistics and Census (INEC) for the years 2020 and 2021 were used. Thus, a probit model was applied to estimate the probability of a male head of household owning a home, and a Propensity Score Matching (PSM) model was applied to evaluate the causal effect of gender, and to see if it really has an impact on home ownership. Based on this, the results of the probit model show a simple correlation or association of gender with respect to homeownership, while the result obtained in the PSM model indicates that gender has a causal and positive influence on homeownership, with male heads of household being more likely to own a home, mainly due to their sociodemographic characteristics. Finally, it is recommended that the authorities implement policies and programs that address gender inequalities in housing. This could be done through the development of financial products, such as credit or mortgage financing, and it would also be important to include financial education to ensure that men and women have access to housing.